Penilaian Erection Hardness Score Pasien Benign Prostatic Hyperplasia yang Ditangani dengan Tamsulosin dan Kombinasi Tamsulosin-Dutasteride - Joko Pitoyo; Bambang S Noegroho; Ricky Adriansjah (Jurnal Ilmu Kedokteran, 2022)
The goal of Benign Prostate Hyperplasia (BPH) therapy is to relieve symptoms and maintain disease progression as well as the side effects of drugs and their benefits for improving the quality of life and sexual quality. This study aimed to assess the effect of tamsulosin therapy with combination therapy of tamsulosin and dutasteride on the erection hardness score (EHS) in men with LUTS due to BPH. This study is a cross-sectional study which assesses and compares differences in erection hardness scores (EHS) of patients with benign prostatic hyperplasia (BPH) before and after tamsulosin therapy and the combination of tamsulosin + dutasteride. After three months of therapy, the group of subjects given tamsulosin had an IPSS score of 12.87 (p=0.00), IIEF-5 15.43 (p=0.51), EHS 2.6 (p=0.08), while the tamsulosin + dutasteride group had an IPSS score 12.53(p=0.00), IIEF-5 15.83 (p=0.02), and EHS 2.6 (p=0.01). The decrease in EHS was more statistically significant in treatment with tamsulosin + dutasteride combination therapy compared with tamsulosin monotherapy, this was due to the effect of each drug combined.